Nghiên cứu ảnh hưởng của chế độ xử lý nhiệt đến cấu trúc và tính chất vật liệu polypropylen ghép anhydrit maleic/nanoclay compozit. Phần I - Ảnh hưởng của chế độ xử lý nhiệt đến sự hình thành cấu trúc vật liệu - Chương, Bùi; Hưng, Đặng Việt (Vietnam Journal of Chemistry, 2014)
In this study, the samples of PPMA/NC were heat treated with various cooling rate. The results of XRD analysis show, that the material was cooled with the lower rate, the formation of exfoliated structure become more favorable. However, cooling rate does not effect on microcrystalline structure of material in whole. It may effect only on crystallization degree. Beside, DSC results show the crystalline structure of PPMA/NC is less perfect in comparison with that of PP-g-MA, that is expressed in lower melting temperature of PPMA/NC.